2013
DOI: 10.1038/bmt.2013.49
|View full text |Cite
|
Sign up to set email alerts
|

CMV reactivation is associated with a lower incidence of relapse after allo-SCT for CML

Abstract: Preemptive therapy at CMV reactivation has diminished post-transplant CMV mortality. Furthermore, recent studies suggest a favorable “virus-versus-leukemia” effect from reactivating CMV, reducing relapse of acute myeloid leukemia (AML) after SCT. We studied the relationship of CMV reactivation with leukemic relapse in 110 patients with chronic myeloid leukemia (CML) receiving HLA-identical sibling SCT between 1993 and 2008. Seventy nine (71.8%) were in chronic phase, 5 in second chronic phase, 17 in accelerate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
62
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 25 publications
4
62
5
Order By: Relevance
“…The virus stimulates a strong Th1 immune response and leads to accumulation of large numbers of cytotoxic cells, including NK and Υδ T cells. CMV infection has been associated with a reduction in disease relapse after stem cell transplantation and may therefore potentially play a role in the setting of other hemopoietic malignancies 34, 35.…”
Section: Discussionmentioning
confidence: 99%
“…The virus stimulates a strong Th1 immune response and leads to accumulation of large numbers of cytotoxic cells, including NK and Υδ T cells. CMV infection has been associated with a reduction in disease relapse after stem cell transplantation and may therefore potentially play a role in the setting of other hemopoietic malignancies 34, 35.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ito et al reported a beneficial effect of CMV reactivation in 110 CML patients with regard to relapse. 5 Manjappa et al found a beneficial effect of CMV reactivation only in AML patients after allogeneic hematopoietic stem cell transplantation with a myeloablative conditioning regimen, 10 whereas Cichocki et al contrast that by reporting a protective effect of CMV viremia in a cohort of patients receiving reduced conditioning only. 17 The study patients had received (in majority) cord blood transplants, which consisted of different immune cell subpopulations and may have had differences in the hematopoietic progenitor cell source, which might have influenced the CMV-induced immune reaction.…”
mentioning
confidence: 94%
“…1 In contrast, we and others have published that CMV reactivation correlates with substantially improved reduction of relapse incidence in patients with AML after transplant. [2][3][4][5][6][7][8][9][10] The antileukemic effect of CMV reactivation is pronounced in AML and chronic myeloid leukemia (CML), but is detectable to a lesser extent in myelodysplastic syndrome (MDS), acute lymphoblastic leukemia (ALL), non-Hodgkin lymphoma, and pediatric acute leukemia. [3][4][5][6][7][8][9][10] We defined this remarkable phenomenon as a virus-versus-leukemia effect, which is rare in hematology and contrary to the effects of oncovirus causing cancer or hematological malignancies such as hepatitis B and C virus, Epstein-Barr virus, human T-lymphotropic virus, Kaposi sarcoma-associated herpes virus, and human papilloma virus.…”
mentioning
confidence: 99%
“…[1][2][3] This was demonstrated in acute myeloid leukemia (AML) and chronic myeloid leukemia (CML). 4 Other studies have demonstrated both early and late protective effects, but all have been on matched related or unrelated donors. + NK cells following CMV reactivation as the potential immunomodulatory mechanism.…”
mentioning
confidence: 99%